Answer:
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
Step-by-step explanation:
The given expression is
![\sqrt{x+3}+4=5](https://tex.z-dn.net/?f=%5Csqrt%7Bx%2B3%7D%2B4%3D5)
We group the constant terms on the right hand side to obtain;
![\sqrt{x+3}=5-4](https://tex.z-dn.net/?f=%5Csqrt%7Bx%2B3%7D%3D5-4)
![\Rightarrow \sqrt{x+3}=1](https://tex.z-dn.net/?f=%5CRightarrow%20%5Csqrt%7Bx%2B3%7D%3D1)
We square both sides of the equation to remove the square root.
![\Rightarrow (\sqrt{x+3})^2=1^2](https://tex.z-dn.net/?f=%5CRightarrow%20%28%5Csqrt%7Bx%2B3%7D%29%5E2%3D1%5E2)
![x+3=1](https://tex.z-dn.net/?f=x%2B3%3D1)
This will simplify to;
![x=1-3](https://tex.z-dn.net/?f=x%3D1-3)
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
I am assuming you wrote the problem wrong. Is it a^2?
A^2 -4A-21=0
(A-7)(A+3)=0
A=7 A=-3, ignore the negative number because it doesn't make sense if you plug in for a.
length=a+3=7+3=10
Width=7=a
Set the equation to 125.
15x+50= 125
Subtract 50.
15x= 75
Divide by 15 into both sides.
x= 5
5 family members went.
I hope this helps!
~cupcake
The 2 angles add up to 90 degrees so
x + y = 90, also:-
x - y = 72 (given)
adding the 2 equations:-
2x = 162
x = 81
and therefore
y + 81 = 90
y = 9
Answer the 2 angles are 81 and 9 degrees